Intelligent Systems for Sustainable Person-Centered Healthcare - Kriksciuniene, Dalia; Sakalauskas, Virgilijus; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This open access book establishes a dialog among the medical and intelligent system domains for igniting transition toward a sustainable and cost-effective healthcare. The Person-Centered Care (PCC) positions a person in the center of a healthcare system, instead of defining a patient as a set of diagnoses and treatment episodes. The PCC-based conceptual background triggers enhanced application of Artificial Intelligence, as it dissolves the limits of processing traditional medical data records, clinical tests and surveys. Enhanced knowledge for diagnosing, treatment and rehabilitation is captured and utilized by inclusion of data sources characterizing personal lifestyle, and health literacy, and it involves insights derived from smart ambience and wearables data, community networks, and the caregivers$1 (Bfeedback. The book discusses intelligent systems and their applications for healthcare data analysis, decision making and process design tasks. The measurement systems and efficiency evaluation models analyze ability of intelligent healthcare system to monitor person health and improving quality of life. .s
Analysis and conceptualization of healthcare systems in the context of technological innovation and personalization -- Person-centred care, theory, operationalisation and effects -- Person-Centred Care Implementation: Design and Evaluation Considerations -- Person-Centred Care Interventions in Pharmaceutical Care -- Shared decision making -- Advancement of efficiency evaluation for healthcare -- An overview of measurement systems and practices in healthcare systems applied to person-centred care interventions -- Studying the impact of human resources on the efficiency of healthcare systems and person-centred care -- Overview of the artificial intelligence methods and analysis of their application potential -- Discovering healthcare data patterns by artificial intelligence methods.
Keywords: Computational intelligence; Biomedical engineering; Computational Intelligence; Biomedical Engineering and Bioengineering